Three-phase fracturing in granular material - Bjornar Sandnes (Geophysical research Abstracts, EGU2015, 2015)
There exist numerous geo-engineering scenarios involving the invasion of a gas into a water-saturated porousmedium: in fracking, this may occur during the fracking process itself or during subsequent gas penetration intopropant beds; the process is also at the heart of carbon dioxide sequestration.We use a bed of water-saturated glass beads confined within a Hele-Shaw cell as a model system to illuminatethese processes. Depending on packing density, injection rate and other factors, air injected into this systemmay invade in a broad variety of patterns, including viscous fingering, capillary invasion, bubble formation andfracturing. Here we focus primarily on the latter case.Fracturing is observed when air is injected into a loosely packed bed of unconsolidated granular material.Our approach allows us to image the complete fracture pattern as it forms, and as such to study both thetopographical properties of the resulting pattern (fracture density, braching frequency etc) and the dynamics of itsgrowth.We present an overview of the fracturing phenomenon within the context of pattern formation in granularfluids as a whole. We discuss how fracturing arises from an interplay between frictional, capillary and viscousforces, and demonstrate the influence of various parameters on the result.